Between Silence and Survival: Social Stigma and Disclosure Dilemmas Among MSM in HIV Prevention Efforts - Rif'ah, Erwin Nur; Putri, Dhea Ninda; Rokhmah, Dewi (Universitas Airlangga, 2025)
Background: For more than three decades, the HIV epidemic in Indonesia has continued to grow and has primarily affected men who have sex with men (MSM). The high prevalence of HIV is inseparable from triggering stigma and discrimination. This hampers prevention and treatment, and encourages many MSM in Indonesia to hide their identity and sexual orientation, so that difficulties in accessing HIV prevention and treatment services and increase the risk of HIV transmission. Self-disclosure is an important aspect for MSM to help prevent HIV transmission and improve treatment adherence. Methods: This study employed a qualitative phenomenological approach using snowball sampling. Data were collected via in-depth interviews and analyzed using the interpretative phenomenological analysis (IPA) method to explore the dynamics of self-disclosure through the lens of the Johari Window theory, focusing on hidden and blind areas. Results: The findings reveal that MSM often conceal their sexual orientation and HIV status due to fear of stigma and discrimination, especially from family, workplace, and social circles representing the hidden area. Meanwhile, the blind area emerges when the environment perceives MSM's identity without explicit disclosure, sometimes offering support but also reinforcing societal pressure. These dynamics significantly affect MSM's willingness to seek help and disclose critical information necessary for HIV prevention. Conclusion: Self-disclosure among MSM is significantly influenced by stigma, discrimination, and the social environment which either supports or hinders their openness. To address this, inclusive and stigma-reducing strategies are urgently needed, particularly within healthcare services.